PENGARUH KUALITAS LAYANAN KENTUCKY FRIED CHICKEN BEKASI TRADE CENTER TERHADAP KEPUASAN KONSUMEN - Indra Jaya; Eva Fauziana (Institut Bisnis Muhammadiyah Bekasi, 2023)
The purpose of this study is to focus on the analysis to determine whether there is an effect of service quality on customer satisfaction in the Kentucky Fried Chicken Bekasi Trade Center. The distribution of questionnaires to 150 consumers of Kentucky Fried Chicken Bekasi Trade Center with a sampling technique using purposive sampling. The research method used is the descriptive quantitative method. The data analysis technique uses descriptive analysis testing, research instrument testing, classical assumption testing, simple linear regression analysis hypothesis testing, and testing the coefficient of determination (R^2) with the help of the SPSS version 25 application program. The results of this study indicate that service quality has a positive effect on customer satisfaction at Kentucky Fried Chicken Bekasi Trade Center by 23.039 > 1.976 and 0.000 < 0.05. While the coefficient of determination (R^2) of the effect of service quality on customer satisfaction at Kentucky Fried Chicken Bekasi Trade Center is 78.2% and the influence of other variables outside this study is 21.8%.